Epistaxis Associated with Theileriosis and its Management in a Buffalo - A Case Report - Prajapati, Ankit S; Parmar, Jignesh J; Chauhan, Vandip D; Shah, Aditya I; Parikh, Pinesh V (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
that cause bovine theileriosis, are spread by ticks  Hyalomma and Rhipicephalus, respectively. Bovine theileriosis  results in severe livestock losses as well as financial losses on  a global scale (Sharma et al., 2017). Apart from bovine, sheep  and goats are also affected by this condition (Prajapati et al.
Keywords: Epistaxis; Theileriosis